Augmentation Mastopexy with Surgical Excision of the Lower Pole to Avoid Waterfall Deformity: A Surgical Technique and Nipple Areolar Complex Case Series. Issue 2 (May 2021) - White, Colin P.; Peterson, Brian D.
Purpose of this article is to demonstrate a way of avoiding the waterfall deformity in augmentation mastopexy patients. We will show a case series of results and explain how this technique gives satisfying aesthetic results for patients seeking breast augmentation who also require mastopexy. We will show how addressing the breast parenchyma on the lower pole via direct excision can give reliable results and avoids the waterfall deformity. The surgical technique used by the senior author combines the principles of breast augmentation, mastopexy, and breast reduction. We apply these principles during the initial single operation. Our goal is to achieve the best anatomical results for the patient. We describe 1538 consecutive patients whom underwent single-stage breast augmentation with mastopexy. All implants were submuscular with 12% being saline and 88% were silicone implants. Vertical mastopexies were performed in 8% and wise pattern incisions were used in 92%. There were no life-threatening complications such as deep vein thrombosis, pulmonary embolism, and so on. Tissue-related complications included wound infection (1%) and hematomas (1%). Implant-related complications included malposition or implant displacement 9% and capsular contracture 1%. Aesthetic complications included dystopia of NAC (4%) and volume asymmetries (10%). Revision surgery was tissue related (2%), implant related (3%), and aesthetic related (10%). There were no cases of waterfall deformity seen in the cohort. In conclusion, we believe that the technique detailed here is easy to do, uses principles already known of breast augmentation and reduction and gives consistent results with low reoperation rates.